The Efficient Synthesis of Dithieno[3,4-b:3',4'-d]thiophene - Xu, Li; Wang, Zhen; Xu, Kun; Shi, Jianwu; Wang, Hua (Letters in Organic Chemistry, 2009)
The efficient synthesis of dithieno[3,4-b:3',4'-d]thiophene was improved by the introduction of TMS groups in four synthetic steps including TMS protection, sulfidation, intramolecular cyclization, and TMS removal. The total yield is 55-63% with 3,4-dibromothiophene as starting material. In addition, the crystal structure of (TMS)4-dithieno[3,4-b:3',4'- d]thiophene was described.
Keywords: TMS protection